The FIFA Regulations on the Labor Regulations and Transfer of Player - Colucci, Michele; Majani, Felix (Indonesian Journal of International Law, 2008)
Like a job in general, the athletes like a footballer bend to the regulations. There are some regulations for them and their boss (clubs), in the international level there are the regulations made by Federation Internationale de Football Association (FIFA). This article is trying to analyze how the FIFA regulations about the employment relations between the club and player by taking the case from two main international arbitration court, the FIFA Dispute Resolution Chamber and the Court of Arbitration of Sport.